Robots [ an important place in world industry (Understanding Robotics, 2005)
Robots play an ever increasing role in industry, particularly where consistency and precision are required. This video series shows students how robots work...their capabilities and limitations...and how they will influence the future. Learn what a robot is and how it compares to human workers. View robots at work performing a variety of jobs; examine the benefits and liabilities of robots and the need